Hodnocení finanční situace mezinárodně působícího podniku a návrhy na jeho zlepšení - Maleček, Jakub (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Diplomová práce je zaměřena na zhodnocení finanční situace vybraného mezinárodně působícího podniku a na základě analyzovaných dat navržení vhodných opatření pro zlepšení finanční situace podniku. Práce je rozdělena do tří částí. První část práce se zabývá definováním pojmů analýzy vnějšího a vnitřního prostředí podniku, finanční analýzy a mezipodnikového srovnání. Druhá část je zaměřena na aplikaci jednotlivých postupů definovaných v části teoretické, tedy analýzy vnitřního a vnějšího prostředí společnosti, finanční analýzy a mezipodnikového srovnání. Poslední část práce, která vychází z výsledků části analytické se věnuje vlastnímu návrhu řešení zlepšení finanční situace podniku.

The diploma thesis is focused on the evaluation of the financial situation of a selected internationally operating company and on the basis of the analysed data to propose appropriate measures to improve the financial situation of the company. The thesis is divided into three parts. The first part of the thesis deals with defining the concepts of analysis of the external and internal environment of the enterprise, financial analysis and inter-enterprise comparison. The second part focuses on the application of the individual procedures defined in the theoretical part, i.e. analysis of the internal and external environment of the company, financial analysis and inter-company comparison. The last part of the thesis, which is based on the results of the analytical part, is devoted to the actual proposal of a solution to improve the financial situation of the company.
Evaluation of the financial situation of a selected internationally operating company and suggestions for its improvement
Keywords: Finanční analýza; mezipodnikové srovnání; analýza vnitřního a vnějšího prostředí; rozdílové ukazatele; SIAD s.r.o.; technické plyny; medicinální plyny; speciální plyny; Financial analysis; inter-company comparison; analysis of internal and external environment; difference indicators; SIAD s.r.o.; technical gases; medical gases; special gases